Advances in the Regulation of Epidermal Cell Development by C2H2 Zinc Finger Proteins in Plants - Han, Guoliang; Li, Yuxia; Qiao, Ziqi; Wang, Chengfeng; Zhao, Yang; Guo, Jianrong; Chen, Min; Wang, Baoshan (Frontiers in Plant Science, 2021)
Plant epidermal cells, such as trichomes, root hairs, salt glands, and stomata, play pivotal roles in the growth, development, and environmental adaptation of terrestrial plants. Cell fate determination, differentiation, and the formation of epidermal structures represent basic developmental processes in multicellular organisms. Increasing evidence indicates that C2H2 zinc finger proteins play important roles in regulating the development of epidermal structures in plants and plant adaptation to unfavorable environments. Here, we systematically summarize the molecular mechanism underlying the roles of C2H2 zinc finger proteins in controlling epidermal cell formation in plants, with an emphasis on trichomes, root hairs, and salt glands and their roles in plant adaptation to environmental stress. In addition, we discuss the possible roles of homologous C2H2 zinc finger proteins in trichome development in non-halophytes and salt gland development in halophytes based on bioinformatic analysis. This review provides a foundation for further study of epidermal cell development and abiotic stress responses in plants.